Effective Dose from Stray Radiation for a Patient Receiving Proton Therapy for Liver Cancer - Taddei, Phillip J (2009)
Because of its advantageous depth-dose relationship, proton radiotherapy is an emerging treatment modality for patients with liver cancer. Although the proton dose distribution conforms to the target, healthy tissues throughout the body receive low doses of stray radiation, particularly neutrons that originate in the treatment unit or in the patient. The aim of this study was to calculate the effective dose from stray radiation and estimate the corresponding risk of second cancer fatality for a patient receiving proton beam therapy for liver cancer. Effective dose from stray radiation was calculated using detailed Monte Carlo simulations of a double-scattering proton therapy treatment unit and a voxelized human phantom. The treatment plan and phantom were based on CT images of an actual adult patient diagnosed with primary hepatocellular carcinoma. For a prescribed dose of 60 Gy to the clinical target volume, the effective dose from stray radiation was 370 mSv; 61% of this dose was from neutrons originating outside of the patient while the remaining 39% was from neutrons originating within the patient. The excess lifetime risk of fatal second cancer corresponding to the total effective dose from stray radiation was 1.2%. The results of this study establish a baseline estimate of the stray radiation dose and corresponding risk for an adult patient undergoing proton radiotherapy for liver cancer and provide new evidence to corroborate the suitability of proton beam therapy for the treatment of liver tumors.